2021
DOI: 10.1109/jiot.2021.3050775
|View full text |Cite
|
Sign up to set email alerts
|

Realizing an Effective COVID-19 Diagnosis System Based on Machine Learning and IoT in Smart Hospital Environment

Abstract: The aim of this study to propose a model based on Machine Learning (ML) and Internet of Things (IoT) to diagnose patients with COVID-19 in smart hospitals. In this sense, it was emphasized that by the representation for the role of ML models and IoT relevant technologies in smart hospital environment. The accuracy rate of diagnosis (classification) based on laboratory findings can be improved via light ML models. Three ML models, namely, Naive Bayes (NB), Random Forest (RF), and Support Vector Machine (SVM), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
124
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 168 publications
(127 citation statements)
references
References 28 publications
1
124
1
1
Order By: Relevance
“…These studies suggested a method to protect sensor data and enhances the performance of big-data analysis in the system. Dynamic and adaptive optimization heuristics, such as genetic algorithm and reinforcement aware schemes, were suggested [2,5,23,[25][26][27]. The different objectives were obtained, such as the cost, security, response time and energy of sensors devices during offloading and scheduling in the IoMT network.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies suggested a method to protect sensor data and enhances the performance of big-data analysis in the system. Dynamic and adaptive optimization heuristics, such as genetic algorithm and reinforcement aware schemes, were suggested [2,5,23,[25][26][27]. The different objectives were obtained, such as the cost, security, response time and energy of sensors devices during offloading and scheduling in the IoMT network.…”
Section: Related Workmentioning
confidence: 99%
“…Fog-cloud is a cooperative computing network where remote cloud offers via internet and fog computing provide services at the edge of the network [4]. Many healthcare applications have been developed based on the IoMT system, where many patients practised these applications with mobile devices [5]. Simultaneously, healthcare sensors are directly connected to the fog-cloud servers to perform any healthcare task for patients [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The model exhibited an accuracy between 94 and 96%. K. H. Abdulkareem et al [ 27 ] proposed a machine learning and IoT based framework to diagnose COVID-19. The study uses Naïve Bayes, Support Vector Machine and random forest for the classification task and reports the highest achieved accuracy (SVM) to be 95%.…”
Section: Related Workmentioning
confidence: 99%
“…In the blood work group, we identified efforts to predict COVID-19 infection based on results from blood, urine, or other laboratory tests. In [ 24 ], the authors reported a sensitivity of 0.93 and a specificity of 0.9333, with an SVM classifier trained with a dataset with 18 blood values. Another work [ 25 ], reported a sensitivity of 0.75 and a specificity of 0.49 using a dataset with laboratory findings (features) to train an XGBoost classifier.…”
Section: Introductionmentioning
confidence: 99%